1991
DOI: 10.1021/bi00218a005
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization from rat liver cytosol of a GDP dissociation inhibitor (GDI) for liver 24K G, a ras p21-like GTP-binding protein, with properties similar to those of smg p25A GDI

Abstract: A regulatory protein for a liver GTP-binding protein (G protein) with a molecular weight value of 24,000 (24K G), which we have recently purified, was purified to near-homogeneity from rat liver cytosol and characterized. This regulatory protein, designated here as GDP dissociation inhibitor for 24K G (24K G GDI), inhibited the dissociation of GDP from and the subsequent binding of GTP to 24K G. 24K G GDI was inactive for other ras p21/ras p21-like small G proteins including c-Ha-ras p21, rhoB p20, smg p21B, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Previ-236 ously it has been reported that rab GDI will inhibit dissociation of GDP from rab3A, rabll and Sec4 [26,28,29]. Rab GDI can also regulate the subcellular localization of rab3A by causing the dissociation of GDP-bound rab3A from synaptic membranes and vesicles [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previ-236 ously it has been reported that rab GDI will inhibit dissociation of GDP from rab3A, rabll and Sec4 [26,28,29]. Rab GDI can also regulate the subcellular localization of rab3A by causing the dissociation of GDP-bound rab3A from synaptic membranes and vesicles [27].…”
Section: Discussionmentioning
confidence: 99%
“…By forming a stable soluble complex with prenylated, GDP-bound rab3A, rab3A GDI will prevent attachment of rab3A to membranes [27]. Rab3A GDI can also slow the dissociation of GDP from Sec4 [28] and rabll [29] and will regulate the membrane association of numerous rab proteins [30,31]. Because rab3A GDI has now been shown to be active on many members of the rab family, the protein has been renamed rab GDI [31].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The source of the AV membranes in mammalian cells is controversial: some studies (Dunn, Jr, 1990;Ericsson, 1969;Novikoff and Shin, 1978;Ueda et al, 1991) have identified endoplasmic reticulum (ER) proteins on the AVi, others detected Golgi membrane proteins (Locke and Sykes, 1975;Yamamoto et al, 1990). The unusual morphological properties of AVs has also led to the hypothesis that these membranes are derived from a unique type of membrane, called a phagophore (Seglen et al, 1990), or isolation membrane ).…”
Section: Introductionmentioning
confidence: 99%